Effect of the inclination angle of the condenser on the heat transfer coefficient value – experimental study - Charun, Henryk; Czapp, Marian; Czapp, Stanisław; Orłowska, Magdalena (Advances in Mechanical and Materials Engineering)
Considering problem of the condensation of the refrigerant in a flow inside channel, the attention should be paid to the shape of its cross-section, the hydraulic diameter, the channel length as well as the orientation of the channel axis in space (horizontal, vertical, inclined). This paper presents an experimental study concerning the effect of the inclination angle of the condenser with a single coil pipe on the heat transfer coefficient value. In the laboratory test the air-cooled condenser with R410A refrigerant has been investigated. The results of test have proved that during the condensation in a single inclined pipe channel there is a specific value of the inclination angle at which the highest value of the heat transfer coefficient is obtained.